Primary cutaneous mucormycosis caused by Mucor irregularis. (25th March 2015) - Xia, X. J.; Shen, H.; Liu, Z. H.
Summary: We describe a case of primary cutaneous mucormycosis in a 44‐year‐old man with an 18‐month history of infiltrative erythematous plaques and haemorrhagic crusting on the dorsum of his left hand. The isolate was identified as Mucor irregularis (formerly Rhizomucor variabilis ) based on the fungus morphology and DNA sequencing results. Improvement was observed after a 6‐month treatment course of itraconazole. No recrudescence was seen during a follow‐up of 23 months after treatment.